PEMBELAJARAN KONTEKSTUAL PENDIDIKAN AGAMA ISLAM : PERSPEKTIF IBNU KHALDUN - Wulandari, Sari; Amaliyah, Amaliyah; Hadiyanto, Andy (Tarbiyatuna : Kajian Pendidikan Islam, 2020)
This study aims to describe: 1) the objectives of Islamic Education according to Ibn Khaldun, 2) the concept of contextual learning according to Ibn Khaldun, 3) the relevance of Ibn Khaldun's educational thought to modern contextual learning. The research method used in this study is library research. While the analytical method used is descriptive qualitative. The results of this study indicate that, 1) the purpose of Ibn Khaldun's contextual learning is to form a perfect human person, while at the same time forming a human personality to be able to live in society, 2) the concept of contextual learning according to Ibnu Khaldun is practically realistic, namely the concept of learning oriented to experience and realistic towards the needs of human life, 3) Ibn Khaldun's educational thought is relevant to modern contextual learning.